Comparative Study Between the Indian and UAE Copyright Law - Sharma, Gaurika; Sharma, Aditi (Trinity Law Review, 2023)
This paper aims to understand and observe laws of Intellectual Property Rights. The main focus is the protection of Copyright laws in Cinematographic Films all over the world. With the emergence of OTT (Over the top) platforms like Netflix, Amazon Prime, and other internet applications and features like Youtube, Spotify, and Instagram reels (especially since Covid), it is necessary to know how copyright affects which country in which sense and how a material shall be protected from different issues like language, adaptations, copying or inspiration in modern forms. We shall research in this paper comparison of copyright laws of Europe and India in order to understand the loopholes and gaps in the protection of literary or artistic works on an international level. The nature and jurisdiction of the protection differ in every country, and hence the expected protection cannot be absolute. This paper shall also focus on steps that shall be taken to keep the original author safe internationally.
Keywords: Law; nature; rights; IP